(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The most important writing more than two and a half decades ago on Indian politics was The Politics in India by Rajni Kothari. Kothari incorporates in his perspective a semblance of modernization and politicization. Modernization of polity implies political development as a long term process assuming relative openness of the political system. Modernation does not imply non-incorporation of the legacy of a long tradition, historical culture, and social and cultural solidarities. Kothari is of the opinion that the social systems provided a key to social solidarity, hence transformation of social system must be a tune with new political institutions and opportunities, and legitimation of the new institutions must be sought in terms of the nature of the social system. Kothari very clearly explains that the context of political development in India is such that it seeks to incorporate into the womb the best elements of the culture of the modern world, without, at the same time, destroying its age-old traditions and diversities.